The Relationship of Non-Food Consumption Expenditures, Early Marriage, Proper Sanitation and Active Posyandu on Stunting in Indonesia 2017-2021 - Windarti Lutfia Sukadi, Tri; Ratih, Arivina (International Journal of Social Science, Education, Communication and Economics, 2024)
Stunting describes chronic malnutrition status during growth and development since early life. In the National Medium Term Development Plan (RPJMN) 2020 - 2024, the Indonesian government set a target for the prevalence of stunting in children under five to only 14% in 2024 (Presidential Decree Number 18 of 2020 concerning RPJMN 2020 - 2024). Efforts were made to see the relationship that causes stunting, non-food consumption expenditure, early marriage, proper sanitation and active posyandu. This research is a type of descriptive research with a quantitative approach using logistic regression with data obtained through the Central Statistics Agency (BPS) for 2017-2021. The Wald test results show that the Non-Food Consumption Expenditure variable receives H0, meaning that there is a negative and significant influence between non-food consumption expenditure on stunting. The variables of early marriage, proper sanitation and active posyandu reject H0, which means that in this study there is a positive and significant influence on stunting. The results of the omnibus test (F) show that the calculated f value is greater than the f table (4.951 > 2.43) with a significance level of (0.000 < 0.05), so H0 is rejected, and Ha is accepted. So, it can be concluded that non-food consumption expenditure, early marriage, proper sanitation and active posyandu simultaneously influence the stunting rate.